Student Character Building Based on Honesty Values and Academic Ethics Through Anti-Corruption Education - Zufarnesia, Zufarnesia; Bibella Rosyanti Kristiani Hutasoit (International Journal of Synergy in Law, Criminal, and Justice, 2026)
Corruption within educational institutions, manifesting in forms such as plagiarism, proxy attendance, and the abuse of organizational power, poses a serious challenge to the role of students as a moral force. This research aims to analyze the contribution of anti-corruption education in shaping student character based on the principles of honesty and academic ethics. Utilizing a descriptive qualitative methodology and an empirical legal approach, this study examines the phenomena within the Accounting Study Program at Mandiri Bina Prestasi University for the 2024 and 2025 periods. Data were collected through closed-ended questionnaires from 50 respondents and analyzed using triangulation techniques to ensure the validity of the findings. The results indicate that anti-corruption education has a significant positive impact on internalizing the Corruption Eradication Commission's (KPK) nine integrity values, particularly through the alignment of materials with real campus issues, such as the rejection of academic fraud and the misuse of technology. However, its effectiveness still faces challenges, specifically the discrepancy between normative values and structural reality, referred to as the "institutional ethics gap." This study concludes that strengthening character with integrity requires a comprehensive integration of honesty values into the curriculum, alongside the support of exemplary role models from educators, to realize a corruption-free educational ecosystem